Nitrogen-Doped Mesoporous Carbon Microspheres by Spray Drying-Vapor Deposition for High-Performance Supercapacitor - Sun, Xiaoran; Kong, Yueqi; Liu, Yang; Zhou, Liang; Nanjundan, Ashok Kumar; Huang, Xiaodan; Yu, Chengzhong (Frontiers in Chemistry, 2020)
Nitrogen-doped mesoporous carbon microspheres have been successfully synthesized via a spray drying-vapor deposition method for the first time, using commercial Ludox silica nanoparticles as hard templates. Compared to freeze-drying and air-drying methods, mesoporous carbon with a higher packing density can be achieved through the spray drying method. Vapor deposition of polypyrrole followed by carbonization and etching is beneficial for the generation of ultra-thin carbon network. The mesoporous carbon microspheres possess a mesopore-dominate (95%) high surface area of 1528 m2 g-1, a wall thickness of 1.8 nm, and a nitrogen content of 8 at% in the framework. Benefiting from the increased apparent density, high mesopore surface area, and considerable nitrogen doping, the resultant mesoporous carbon microspheres show superior gravimetric/volumetric capacitance of 533.6 F g-1 and 208.1 F cm-3, good rate performance and excellent cycling stability in electric double-layer capacitors.